A compendium of socio-economic statistics for the AOSERP study area since 1961 ... - Inc., Urban Dimensions Group (University of Alberta Library, 1980)
The central objective of the study entitled \"A Compendium of Socio-Economic Statistics for the Athabasca Oil Sands Region\" was to assemble data that would facilitate an understanding of the demographic and socio-economic impacts of oil sands development in the Fort McMurray area and, where possible, Fort Chipewyan, Fort Mackay and Anzac. A further requirement of the study was that these data, where possible, be taken back to 1961. The requirements that the various types of socioeconomic and demographic data be comparably measured over time, and the need to relate these data to specific geographical areas, has limited the types of data sources relevant to this study. In particular, we have found data from the Census of Canada, for the years 1961, 1966, 1971 and 1976, to be the most satisfactory means of meeting these requirements of temporal and geographical continuity. Even so, these data have required various standardization procedures. Where possible, census data have been augmented with data obtained ...